2001
DOI: 10.1111/j.1755-0238.2001.tb00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of polysaccharides by yeasts and the influence of released polysaccharides on colour stability and wine astringency

Abstract: Release of polysaccharides by three strains of Saccharomyces cerevisiae during alcoholic fermentation in synthetic medium and red wine was studied. Polysaccharides after isolation from media by ethanol precipitation were quantified by a colourimetric method as well as by HPLC assay in wines. Yeast strains differed in their capacity to release polysaccharides into the medium and a maximum concentration of 100mg/L was observed. For all strains, release varied according to metabolic phase, with greater release oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
169
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(181 citation statements)
references
References 17 publications
10
169
2
Order By: Relevance
“…Moreover, Domizio et al [21] showed that S. japonicus releases significant amounts of polysaccharides as compared to S. pombe, thus outlining another possible utilization for these non-Saccharomyces wine yeasts in the winemaking industry. Indeed, yeast polysaccharides have many positive effects on wine quality, as they contribute to reducing protein and tartrate instability [23][24][25][26][27][28], increase the 'fullness' sensation [29], and interact with polyphenols aggregates, thus smoothing the perception of astringency [30][31][32], and retaining aromatic compounds [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Domizio et al [21] showed that S. japonicus releases significant amounts of polysaccharides as compared to S. pombe, thus outlining another possible utilization for these non-Saccharomyces wine yeasts in the winemaking industry. Indeed, yeast polysaccharides have many positive effects on wine quality, as they contribute to reducing protein and tartrate instability [23][24][25][26][27][28], increase the 'fullness' sensation [29], and interact with polyphenols aggregates, thus smoothing the perception of astringency [30][31][32], and retaining aromatic compounds [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…They are known for several important interactions and properties in wines, having the ability to inhibit the crystallisation of tartaric salts (Moine-Ledoux & Dubourdieu, 2002), prevent protein haziness (Waters et al, 1994), interact with phenolic compounds (Vasserot et al, 1997;Escot et al, 2001;Riou et al, 2002;Poncet-Legrand et al, 2007) and reduce red wine astringency (Guadalupe et al, 2007(Guadalupe et al, , 2010, enhance and interact with some wine aromas (Chalier et al, 2007), enhance the growth of malolactic bacteria (GuillouxBenatier et al, 1995), promote flocculation in sparkling wines (Nunez et al, 2006) and adsorb ochratoxin A (Baptista et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A positive correlation between the autolytic capacity of yeast strains and the quality of the sparkling wines obtained has been shown by several groups of workers (2,13,20,21). However, autolysis in enological conditions is a slow process that requires long aging periods in order to obtain the desired results, which contributes to the relatively high production costs of these wines.…”
mentioning
confidence: 96%